Cholesterol modulates the organization of the gammaM4 transmembrane domain of the muscle nicotinic acetylcholine receptor. - de Almeida, R; Loura, L; Prieto, M; Watts, A; Fedorov, A; Barrantes, F (2004)
A 28-mer gammaM4 peptide, obtained by solid-state synthesis and corresponding to the fourth transmembrane segment of the nicotinic acetylcholine receptor gamma-subunit, possesses a single tryptophan residue (Trp453), making it an excellent model for studying peptide-lipid interactions in membranes by fluorescence spectroscopy. The gammaM4 peptide was reconstituted with synthetic lipids (vesicles of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, i.e., POPC) rich and poor in cholesterol and analyzed using steady-state and time-resolved fluorescence techniques. The decrease in gammaM4 intrinsic fluorescence lifetime observed upon incorporation into a cholesterol-rich lo phase could be rationalized on the basis of a dynamic self-quenching owing to the formation of peptide-rich patches in the membrane. This agrees with the low Förster type resonance energy transfer efficiency from the Trp453 residue to the fluorescent cholesterol analog, dehydroergosterol, in the lo phase. In the absence of cholesterol the gammaM4 nicotinic acetylcholine receptor peptide is randomly distributed in the POPC bilayer with its hydrophobic moiety matching the membrane thickness, whereas in the presence of cholesterol the increase in the membrane thickness and variation of the material properties favor the formation of peptide-enriched patches, i.e., interhelix interaction energy is essential for obtaining a stabilized structure. Thus, the presence of a cholesterol-rich, ordered POPC phase drives the organization of peptide-enriched patches, in which the gammaM4 peptide occupies approximately 30% of the patch area.